DEVELOPMENT OF AN E-CLINIC SYSTEM BASED ON A WEBSITE AT TAMARA CLINIC, BATAM CITY - Rinaldi, Muhammad; Anisa, Desfa; Farhansyah, Fani (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
A clinical information system is a collection of diverse information technology applications that offer a centralized repository of patient care-related information across distributed locations. This repository contains the patient's clinical history along with the physician's decisions regarding the patient's condition, treatment choices, and overall health. The clinical information system is defined as a computer-based system dedicated to collecting, storing, and disseminating all essential clinical information required for patient care. Clinical information systems are frequently acknowledged for their potential to enhance the quality of healthcare services. The primary function of a clinical information system is to present tailored information to patients in a clear, organized, and timely manner. One of the clinical information systems employed for data management in clinics is the E-Clinic. This study aims to design and develop a web-based patient registration system for utilization at the Tamara Clinic. This qualitative research employs experimental research methods, involving the creation of a solution during the research process.